a deterministic model for predicting water yield from two different watersheds - Putu Sudira (Indonesian Journal of Geography, 2005)
This study was conducted in Pogung-Code sub watershed and Pulo-Opak sub watershed from 1993 to 2002. A deterministic model developed by Haan (1972) was used to determine the amount of water yield from watersheds. The model consists offour parameters, namely: (0 maximum rate of seepage from the soil water zone in mm per day (S), (ii) maximum soil moisture less readily available for evapotranspiration in mm (C), (iii)fraction ofseepage from the soil water zone that becomes runoff(F), and (iv) maximum infiltration rate in mm per hour (f.).The inputs required by the model were the daily rainfall and the estimated potential evapotranspiration which was computed using Penman method. Streamflow records for 10 years of Pogung-Code sub watershed (2,801.77 ha) and Pulo-Opak sub watershed (4,856.37 ha) were used to test the validity of the model. The parameters obtained for Pogung-Code sub watershed were: S = 0.70 mm per day, C = 112.32 mm, F = 0.63, and- 5.38 mm per hour, meanwhile for Pulo-Opak sub watershed were: S = 2.33 mm per day, C = 86.72 mm, F --- 0.26 and f = 5.68 mm per hour.The final test of the adequacy of the model lay in a comparison of observed and simulated runoff The comparison showed that the observed and simulated runoff values are not significantly different. This was based on the results obtained from statistical measures to test the model. The model did a better simulation in the smaller watershed (Pogung-Code sub watershed) than in the larger one (Pulo-Opak sub watershed).